First radiometric age of Cretaceous deposits of the Central Precordillera - Tedesco, A.M. (2007)
Ciénaga del Río Huaco Formation was deposited during the Cretaceous in the Precordillera Central (La Rioja and San Juan provinces). The unit forms part of a thick red-bed sequence including rocks of different ages (from Late Paleozoic to Tertiary) and problematic identification. In the La Troya river area, the red bed sequence is composed of the Panacán (Permian), Santo Domingo (Late Triassic- Early Jurassic), Ciénaga del Río Huaco (Cretaceous) and Puesto La Flecha Formations (Oligocene- Early Nfiocene). In the past, all these formations were included in the same stratigrapbic unit and only in recent years the different formations could be separated mainly based on their fossil contain. In the case of Ciénaga del Rio Huaco Formation, the finding of microfossils (palynomorphs and ostracods) allowed to infer a Late Cretaceous age for these rocks. However, a radiometric age of 108,1 ± 4,4 Ma presented in this paper, clearly suggest that the unit was deposited at the end of the Early Cretaceous. This age is the first Cretaceous absolute age in the Precordillera Central and enhances the time constraints of of the Cretaceous Basin.